ANALISA STRUKTUR BANGUNAN GEDUNG SEKOLAH AKIBAT PENAMBAHAN RUANG KELAS BARU (STUDI KASUS: SMK YATPI GODONG) - Muhroni, Alim; Wibowo, Agung Hari (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
The study was conducted at the SMK YATPI Godong building which has a land area of 1172 m2. 2017 to 2019 there was an increase in the number of students by 60.2%, so it is necessary to add new classrooms. Where the land area cannot be used to build classrooms horizontally, the school adds classrooms vertically by adding 1 floor to 2 floors. The study was carried out by testing the quality of concrete using the Hammer Test obtained 26.45 MPa, then modeling analysis using SAP 2000 software and manual calculations based on SNI 1729-2019. This analysis is made in 2 stages, first the initial conditions in the existing building, second the analysis of the existing structure with the additional load of the new classroom. Keywords: Structure, School Building, Hammer Test, SAP 2000